Identifikasi dan Pemanfaatan Tumbuhan Obat Tradisional di Resort Habaring Hurung TN Sebangau: Identification And Utilization Of Traditional Medicinal Plants At The Habaring Hurung Resort, TN Sebangau - Rosdiana, Rosdiana; Madiyawati, Milad; Koroh, Desy Natalia; Putir, Patricia Erosa; Sianipar, Ayu Cica Pratiwi (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Indonesia has a high biological wealth, including various types of medicinal plants that are traditionally used by the community. This study aims to identify the types of medicinal plants and their use in Sebangau National Park, especially in the Habaring Hurung Resort. The approach used is descriptive qualitative, with an exploratory survey method. Data were collected through field observations, semi-structured interviews with key informants (traditional leaders, shamans, and local knowledgeable residents), and visual documentation. Research on medicinal plants in the Habaring Hurung Resort, Sebangau National Park, successfully identified 23 species of medicinal plants used in the traditional healing practices of the local community. The species are spread across 16 families, as well as one unidentified species (pari laki) with a dominance of the Lauraceae and Arecaceae families with the most widely used plant parts being the roots, bark and fruit. These findings indicate the great potential of Sebangau National Park as a source of medicinal plants and the importance of preserving the traditional knowledge of local communities